Explaining the Conceptual Model of Valuing Indicators of Urban Housing; Hedonic Method Meta-Analysis - Sedaghati, Atefeh; Pirbabaei, Mohammad Taghi; Nourian, Farshad; Beyti, Hamed (International Journal of Sustainable Construction Engineering and Technology, 2021)
Problem Statement: The Hedonic valuation method has been considered in various fields by researchers in order to estimate the value of a commodity or the demand for exploitation of a commodity for many years. Besides, the "Hedonic method" has been widely used to identify "value" in the housing market. Although the Hedonic model has been used in the housing market for various purposes, a main and practical context of the model has been identifying the indicators that explain the value of housing and the application of these indicators in urban housing planning. Objective: This article tries to develop a "conceptual model" of value and inference from the research of others, by meta-analyzing the existing theoretical literature regarding the valuing indicators in the Hedonic model. Methodology: The present study, which has been done by meta-analysis method, uses MAXQDA software and open and axial coding to analyze the texts in order to compile and classify the features that explain the value of housing. Findings: The research findings, which are taken from 335 highly cited articles between 2009 and 2019, show that despite the long period of application and theoretical development of the model, there is no theoretical consensus on the explanatory indicators of housing value. So that 7 main categories can be identified in the form of 350 concepts and 5883 codes (including frequency) which can show the range of housing value dimensions, in addition to summarizing the issue. Also, the share of basic structural-physical and peripheral categories, with 53.5 and 25.5 percent, respectively, has the most application in the Hedonic housing valuation model. In the two mentioned categories, the share of variables affecting the residential unit, building of the property and access to services and land uses with relative shares of 23.6, 19.2 and 16.5%, is more than other variables. Conclusion: The results show that while the concepts of many explanatory indicators of value are the same, a suitable range of explanatory indicators of housing value can be used in the Hedonic model according to the goals and the target community, and this can lead to the formation of indigenous and specific values of a society.